Associations of Body Mass Index at Different Ages with Early-Onset Colorectal Cancer - Shaista Zeb, Imran Arshad, Prem Kumar, Ehsan Rahim Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: The risk of colorectal cancer is significantly associated with excessive body mass index, the relationship between body fatness at a young age and the risk of colorectal cancer has proven equivocal. The aim of the present study was to assess the association of early-onset colorectal cancer with body mass index at different ages. Methodology: This population-based control case study was conducted on 450 colorectal cancer patients and 410 controls in the department of Gastroenterology, Isra University Hospital, Hyderabad, Pakistan from March 2020 to February 2022. Standardized questionnaire was used for gathering patient’s information such as medical history, sociodemographic, and lifestyle history with interviewers who collected information and data. All the patients with age less than 35 years and had histopathological evidence of colorectal cancer were included in this study. Prior to study conduction, ethical approval was taken from the respective hospital. Multiple regression model was used for estimating colorectal cancer. SPSS version 23 was used for data analysis. Results: The risk of colorectal cancer at early-onset was compared in patients with body mass index of <25 kg/m2 and >30 kg/m2 at age between 20 and 30 years. The diagnosis of interviewers had early-onset CRC fold risk 2.6- (95% confidence interval, 1.19–5.32), 2.1- (confidence interval, 1.3–3.32), and 1.9- (95% confidence interval, 1.29–2.67). The link between BMI and early-onset CRC risk was most significant among, and virtually limited to, the majority of people who had never had a colonoscopy. Conclusion: The present study found that being overweight or obese in early adulthood is closely connected with an increased chance of developing CRC. As a result, data strongly supports the notion that topical increases in the incidence of obesity among younger population may be a contributing cause to the rise in the prevalence of early-onset CRC. Our findings show that interventions to reduce the obesity pandemic in future generations will be important in preventing CRC. Keywords: Early-onset colorectal cancer, Body Mass index, Different Ages